Don't say we didn't warn you : a novel - Dixon, Ariel Delgado (Random House, 2022)
"A young woman thinks she has escaped her past only to discover that she's been hovering on its edges all along: she and her younger sister, Fawn, bide their time in a dilapidated warehouse in a desolate town north of New York City; their parents escaped there with dreams of starting an art commune. But after the girls' father vanishes all traces of stability disappear for the family, and the girls retreat into strange worlds of their own myth-making and isolation. As the sisters both try to survive their increasingly dark and dangerous adolescences, they break apart and reunite repeatedly, orbiting each other like planets. Both endure stints at the Veld Center, a wilderness camp where troubled teenage girls are sent as a last resort, and both emerge more deeply warped by the harsh outdoor survival experiences they must endure, and the attemps by staff to break them down psychologically"--